The Impact of Technological Innovation on The Productivity of The Manufacturing Industry - Miko Mei Irwanto; Olyvia Rosalia; Firayani Firayani; Jacky Chin (Nomico, 2025)
This study aims to analyze the impact of technological innovation on the productivity of the manufacturing industry. Technological innovation in this research includes the use of the Internet of Things (IoT), artificial intelligence (AI), and automation in production processes. The approach used is quantitative, with a linear regression analysis method to examine the relationship between the independent and dependent variables. This study involves respondents from various manufacturing sectors to gain a comprehensive understanding of the impact of technology on operational efficiency. The research findings indicate that technological innovation has a significant influence on productivity improvement, with each technological component contributing differently to production efficiency. The implications of these findings highlight the importance of digital transformation in the manufacturing industry to enhance competitiveness and operational effectiveness. Additionally, this study recommends workforce training and supportive policies for technology adoption to maximize the benefits of innovation in the industrial sector. This study also opens opportunities for further research by considering other factors such as organizational culture and supply chain integration in supporting technology implementation in the manufacturing industry.